Constraints related to smoke-free policy implementation: a review - Minhat, Halimatus; Ah, Siti Hafsah; Raj, Diana; Mohd Razi, Nuurain Amirah; Baharuddin, Mohammad Najib (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2022)
Introduction: Smoke-free policies have been enacted and enforced either by law or voluntarily adapted by countries in order to protect its people from the harms of second-hand smoke. However, the mere adoption of smoke-free policies does not guarantee success in fully achieving smoke-free environments due to the many issues and challenges in implementing the policies. The objective of this review is to identify the issues and challenges in the implementation of smoke free policies worldwide. Materials and Methods: A scoping review on observational study designs was conducted. English published journal articles between 1999 and 2019 were searched in four databases (Ovid Medline, PubMed, Scopus and ScienceDirect) and general search engine from September until December 2019. Relevant articles gathered systematically using PICO elements and combination of suggested Medical Subject headings (MeSH) keywords. Results: Twenty articles were included in this review after the filtering and screening process. The smoke-free policy implementation issues were discussed according to the health-policy framework (Content, Context, Actors and Process). Most of the barriers identified were related to the actor construct reflecting the important role played by smokers specifically and the community in general to support the implementation of the policy. Conclusion: The review highlights the important role played by the author contruct of the health-policy framework in order to successfully implement the smoke-free policy especially involving smokers’ awareness and commitment and also public perception towards the capacity of the authority to enforce the policy.